Solidarne być albo nie być w edukacyjnej przestrzeni - Janus-Sitarz, Anna; Jaskółowa, Ewa; Kwiatkowska-Ratajczak, Maria; Latoch-Zielińska, Małgorzata; Tomaszewska, Grażyna; Szczukowski, Dariusz (Polonistyka. Innowacje, 2023)
-